Hemodialysis Patients’ Experiences of Diet and Fluid Restriction: A Qualitative Study - Bulantekin Duzalan, Özlem; Albayrak Cosar, Arife; Sarikaya, Sibel (Progress in Nutrition, 2021)
Study Objective: Adherence to diet and fluid restriction is one of the most important elements of hemodialysis (HD) treatment. The aim of this study was to explore the methods used by HD patients in adhering to diet and fluid restrictions, and the sources of motivation and experiences affecting adherence. Methods: A qualitative design underpinned by a phenomenological hermeneutical approach was applied. The study was conducted with 14 patients undergoing HD, using the face-to-face interview method. Sound recordings were transcribed to written form, and content analysis. Results: Four themes were determined as a result of the content analysis. These were self-management, sources of motivation, existential struggle and future expectations. In the study, an analysis was made of the difficulties in the socio-cultural field which the HD patients had in adhering to diet and fluid restrictions, and their adherence to diet and fluid restrictions in order to meet their expectations for the future, to live well in the present and to remain alive, and to meet the expectations of their friends and families. Conclusion: It is important in this sense for nurses to evaluate their patients in all dimensions and contribute to their care.